An early Harvard 'Memorandum' on anti-depression policies - David Laidler; Roger Sandilands; L. B. Currie; E. T. Ellsworth; H. D. White (The University of Western Ontario, Department of Economics, 2000)
[Introductory Note by David Laidler (University of Western Ontario) and Roger Sandilands (University of Strathclyde) ...] The Memorandum which this note introduces was completed by three young members of the Harvard economics department sometime in January 1932 Two of them, Lauchlin Currie and Harry Dexter White were soon to play key roles on the American, indeed the world-wide, policy scene. Both of them would go to Washington in 1934 as founding members of Jacob Viner's 'Freshman Brains Trust'. In due course, first at the Federal Reserve Board, and later at the Treasury and the White House, Currie would become a highly visible and leading advocate of expansionary fiscal policy, while White, at the Treasury, was to be a co-architect, with Keynes, of the Bretton Woods system. Both would fall victim to anti-communist witch-hunts in the late 1940s, in White's case perhaps at the cost of his life, since he died of a heart attack in 1948 three days after a strenuous hearing before the House Committee on Unamerican Activities (HUAC). The third author, P. T. Ellsworth, later a Professor of Economics at the University of Wisconsin, is perhaps best remembered nowadays as the author of a leading textbook in International Economics, though it is worth noting that he was also a very early (late 1936) but hitherto unrecognised discoverer of what came to be called the IS-LM model as a means of elucidating issues raised by Keynes' 'General Theory'. It is not known how widely this Memorandum was circulated, but the fact that it is a piece of policy advocacy, combined with its relatively polished style, makes it inconceivable that it was meant for the eyes and files of its authors alone. As readers will see, it sketches out an explanation of the then rapidly developing Great Contraction, as well as a comprehensive and radical policy programme for dealing with it. In keeping with its authors' explanation of the Contraction as a consequence of a collapsing money supply, the main domestic components of that programme were to be vigorously expansionary open-market operations and substantial deficit spending that, particularly in its early stages, was to be financed by money creation; its international dimension involved a return to free trade and serious efforts to resolve the problems of international indebtedness that had originated in the Great War and in the Treaty of Versailles which had brought it to an uneasy end in 1919. [...]
Keywords: 330